Pengaruh Komitmen Organisasi Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Dan Kinerja Karyawan Rumah Sakit Bhayangkara Trijata Denpasar - Ristiana M, Merry (Program Doktor Ilmu Ekonomi, 2013)
Organizational commitment, job satisfaction and Organizational Citizenship Behavior (OCB) are directly related to employee’s performance. Organizational commitment and job satisfaction and Organizational Citizenship Behavior (OCB) experienced by employee could reduce or increase employee’s performance.The purposes of this research are to analyze the influence of organizational commit-ment and job satisfaction towards Organizational Citizenship Behavior and its influence to the employee’s performance.The samples of this research consisted of one hundred and twelve employees’s Bhayangkara Trijata Hospital, Denpasar. Stuctural Equation Model (SEM) was run by an AMOS software for data analysis.The result of the analysis showed that the that organizational commitment, job satisfac-tion have positive influence and significant to Organizational Citizenship behavior and employee’s performance. Organizational Citizenship Behavior have positive influence and significant to employee’s performance. This research also found out that organizational commitment, job satisfaction have positive influence and significant towards Organizatio-nal Citizenship behavior which later also influence the employee’s performance.Key words: organizational commitment, job satisfaction, Organizational Citizenship Beha-vior, employee’s performance.